A first-order logic expression of the CIDOC conceptual reference model. (2018) - Meghini, Carlo; Doerr, Martin
The CIDOC Conceptual Reference Model is a well-known conceptual modelling language for documenting cultural heritage artefacts, with a special attention to museum objects. CRM is an ISO standard since 2006 (ISO21127:2006) and renewed 2014 (ISO21127:2014). The CRM is specified in a semantic data modelling style and relies on consolidated notions for the representation of knowledge such as classes, properties, IsA hierarchies, domain and range constraints and cardinality restrictions. However, the CRM still lacks a formal specification of its semantical and inferential apparatus. This lack makes it difficult to clearly define fundamental operations on a CRM knowledge base, such as querying or consistency checking, while preventing any investigation on the computational properties of the language. This paper provides such an apparatus by expressing the CRM as a first-order theory. It then provides a reduction of the theory to a datalog program, and shows how the program can be used to effectively query a knowledge base taking into account the logical consequences of the represented knowledge.